2008
DOI: 10.1016/j.neulet.2008.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 induces filopodia in differentiated P19 neural cells to facilitate viral spread

Abstract: Herpes simplex virus type-1 (HSV-1) is a neurotropic virus with significant potential as a viral vector for CNS gene therapy. This study provides visual evidence that recombinant green fluorescent protein (GFP) expressing HSV-1 travel down dendrites in differentiated P19 neuronal-like cells to efficiently reach the soma. The virus also promotes cytoskeletal rearrangements which facilitate viral spread in vitro, including often dramatic increases in dendritic filopodia. Viral movements, cell infection and filop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
55
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 34 publications
5
55
0
Order By: Relevance
“…15 Similar findings have been reported with herpes simplex virus type 1 (HSV-1) and African swine fever virus, which appear to induce membrane projections on target cells. 16,17 The relative contribution of these actin-based protrusions during cell-tocell transmission of HIV-1 is currently not fully established, although a recent study has attempted to tackle this question during T cell-T cell transmission of HIV-1, 18 and recent 3D electron microscopic studies of the virologic synapse formed between mature DCs and CD4 ϩ T cells have shown that there are extensive membrane extensions emanating from the DCs that wrap around the T cells.…”
Section: Introductionmentioning
confidence: 99%
“…15 Similar findings have been reported with herpes simplex virus type 1 (HSV-1) and African swine fever virus, which appear to induce membrane projections on target cells. 16,17 The relative contribution of these actin-based protrusions during cell-tocell transmission of HIV-1 is currently not fully established, although a recent study has attempted to tackle this question during T cell-T cell transmission of HIV-1, 18 and recent 3D electron microscopic studies of the virologic synapse formed between mature DCs and CD4 ϩ T cells have shown that there are extensive membrane extensions emanating from the DCs that wrap around the T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cells extend thin cylindrical protrusions known as filopodia during processes such as migration, axon guidance, angiogenesis, phagocytosis, and pathogen invasion (1)(2)(3)(4). These dynamic structures are tubular extensions of the plasma membrane filled with bundles of linear actin filaments, and the cytoskeletal rearrangements leading to their formation are controlled by RhoGTPases such as Cdc42 (5-7) and Rif (8,9).…”
mentioning
confidence: 99%
“…Its N-terminal inverse bin-amphiphysin-Rvs (I-BAR) 3 domain binds to and deforms the plasma membrane, whereas its C-terminal Src homology 3 (SH3) domain interacts with various actin regulators such as neural Wiskott-Aldrich syndrome protein (N-WASP) (7), mammalian enabled (Mena) (6,10), EGF receptor kinase substrate 8 (Eps8) (11), the WASP family verprolin homology (WAVE) isoforms WAVE1 (7) and WAVE2 (7,12), and the mammalian Diaphanous (mDia) isoforms mDia1 (7,13) and mDia2 (7). In the inactive state, the SH3 domain of IRSp53 is hidden by an intramolecular interaction between the N and C termini of the protein.…”
mentioning
confidence: 99%
“…Elucidating the exact mechanism(s) by which filopodia form will give a greater understanding of these cellular processes and how such structures play a role in pathological conditions such as metastasis (3) and pathogen invasion (4,5). The Rho GTPase Cdc42 is a key regulator of cell signaling events that lead to filopodium formation in mammalian cells.…”
mentioning
confidence: 99%
“…Furthermore, knockdown of the Rac effectors WAVE1 and WAVE2 does not disrupt Rif-mediated filopodia formation. Using acceptor photobleaching FRET (AP-FRET) 4 to examine Rif-mDia protein-protein interactions, we found that Rif interacts directly with mDia1 in filopodia but not with mDia2. mDia1 can by itself induce filopodia, and knocking it down inhibits Rif-driven filopodium formation.…”
mentioning
confidence: 99%